2014
DOI: 10.1016/j.ecoleng.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal succession of the vegetation in Xishuangbanna, China during 1976–2010: A case study based on RS technology and implications for eco-restoration

Abstract: a b s t r a c tThe spatial-temporal succession of regional vegetation in Xishuangbanna, China from 1976 to 2010 was studied based on RS technology. The results showed the area fluctuation of main vegetation types in the study area during the research period. There was no great change in the total area of main vegetation, with the fluctuation area ranging from 12,579.84 to 14,698.75 km 2 , averaging 13,664.48 km 2 annually, and with the fluctuation ratio between −7.94% and 7.57%. The area of natural vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Similar patterns arise near giant panda habitats, where ecotourism fails to achieve a mutually beneficial outcome for economic development and nature conservation (Ma et al., 2019). In Xishuangbanna, habitat loss primarily stems from converting forests into artificial plantations, mainly rubber and oil palm (Huang et al., 2014). The expansion of rubber plantations in Xishuangbanna resulted in approximately a 25% decline in the forested area between 1976 and 2014 (Liu et al., 2020), contributing to the functional extirpation of numerous large mammals (Huang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns arise near giant panda habitats, where ecotourism fails to achieve a mutually beneficial outcome for economic development and nature conservation (Ma et al., 2019). In Xishuangbanna, habitat loss primarily stems from converting forests into artificial plantations, mainly rubber and oil palm (Huang et al., 2014). The expansion of rubber plantations in Xishuangbanna resulted in approximately a 25% decline in the forested area between 1976 and 2014 (Liu et al., 2020), contributing to the functional extirpation of numerous large mammals (Huang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to regional differences. Previous studies indicated that the average elevation of Menghai County is 1411.77 m, which is not suitable for rubber planting [62]. In addition, the expansion pattern of rubber plantations on Xishuangbanna was quite different from that of Hainan Island, the rapid expansion of rubber plantation on Hainan Island began in the early 1980s [63].…”
Section: B the Spatial-temporal Dynamic Of Rubber Plantations In Xishuangbannamentioning
confidence: 96%
“…For example, in the study on Loess area, it is found that the change in land use pattern and vegetation spatial pattern would lead to differences in the runoff and sediment yield [ 58 – 60 ]; the analysis on the Picea crassifolia forest in Qilian Mountain, Qinghai, illustrated that the ecological hydrological indexes of forest stands such as total penetrated rainfalls, interception, and trunk stream were greatly influenced by canopy structural characteristics [ 61 ]; the study on the reservoir area of Three Gorges showed that the general ecological hydrological function of the forest ecosystem in the reservoir area was represented as shrub forest > mixed conifer-broadleaf forest, evergreen broad-leaved forest > Phyllostachys pubescens forest > cropland, among which the ecological hydrological function of forest vegetation was 1.12~2.90 times of that of cropland, and the ecological hydrological function of shrub forest was the best [ 62 ], and the list could go on [ 63 ]. There were few reports on the ecological hydrological regulation effects of vegetation in Southwest China 10 years before [ 64 , 65 ]; several years afterwards, there was almost no report, though only in recent years the study on this issue got warm again after a cold spell [ 66 – 70 ]. However, from the general development status quo in such field at home and abroad, the study on the hydrological regulation effects of vegetation was characterized with regional imbalance; namely, it was mostly focused on vegetation in arid or semiarid area, while the study on vegetation in other climatic regions was rather deficient.…”
Section: Study Status Quo and Development Trendsmentioning
confidence: 99%